Pedogênese e diversidade microbiana em planossolos sob processo de desertificação na região semiárida de Pernambuco - NEVES, Laércio Vieira de Melo Wanderley (2018)
The pedological studies in desertification nuclei are scarce mainly by addressing the pedogenesis and microbial diversity. The changes of mineralogical properties, microbial diversity of functional groups linked to N, P, Fe and carbon stock, of Planosols under different levels of degradation, are preponderant factors in the Planosols pedogenesis for defining their edaphic properties. The objectives of this work are to characterize the microbiology, the morphology, the physics, the chemistry , the mineralogy and the micromorphology of Plansols developed on acidic rocks, inserted in the region of the Cabrobó Desertification Nucleus. For that, one Planosol profile was selected in an area with vegetation and another selected in an area without vegetation (degraded area). The profiles were described morphologically. Deformed and undeformed samples were collected for the purpose of physical, chemical, mineralogical, micromorphological, petrographic analyzes, total analysis and selective extraction of iron and the carbon stocks. Also was evaluated the Microbial diversity and the Microbial abundance in its structures by independent cultivation techniques like: Soil Microbial Biomass (BMS), basal respiration, real-time Polymerase Chain Reaction (qPCR) and DGGE (Gel Electrophoresis with Denaturing Gradient ) of functional groups linked to P, N and Fe. The bioavailability of N and P was tested by the abundance of the genes (AOB) involved in the oxidation of ammonium and by the genes linked to alkaline phosphatase (phoD). The fixation of N was tested by nitrogenase activity in acetylene reduction (ARA). The results of the mineralogical and micromorphological analyzes show that the argilation is the main process involved in the formation of the B horizons by the alteration of the feldspars in the Planosols studied. The planosol described in the vegetated area was classified in the SIBCS as SXe1 and its secondary minerals are composed of alumina clays of the beidelite and kaolinite types, with alteration season: feldspar-K / biotite- Ilitabeidelite / kaolinite. While the planosol described in the area without vegetation was classified as SXe2 and has montmorillonite and kaolinite in the clay fraction. Among the main results obtained by the molecular techniques for total bacteria, between the horizons of the same profile and between the evaluated areas, was observed that the pedogenic horizons have different niches with differences in the structures and abundance of microbial communities. The results indicate that there was a possible selection of bacteria induced by depth and by the specific conditions of each horizon (physical and chemical attributes) including genes linked to alkaline phosphatase. Among the diazotrophic microorganisms of free life, diversity was detected in the structures and in the abundance of communities, including the presence of archaeas. The mean values of similarity indicated little separation of diazotrophic communities in SXe1 (area with vegetation) and a clear existence of two distinct communities in SXe2 (area without vegetation). This profile also presented a 50% reduction in the carbon stock in comparison to the SXe1. Nitrogen fixation was confirmed by the activity of the nitrogenase enzyme through the acetylene reduction test (ARA), which showed efficiency in all pedogenic horizons. In addition, the tests with genes related to ammonium oxidant bacteria (AOB) also confirmed the presence of organisms that act in the cycling and availability of nitrogen.